2017
DOI: 10.1111/mmi.13674
|View full text |Cite
|
Sign up to set email alerts
|

The Snf1‐activating kinase Sak1 is a key regulator of metabolic adaptation and in vivo fitness of Candida albicans

Abstract: The metabolic flexibility of the opportunistic fungal pathogen Candida albicans is important for colonisation and infection of different host niches. Complex regulatory networks, in which protein kinases play central roles, link metabolism and other virulence-associated traits, such as filamentous growth and stress resistance, and thereby control commensalism and pathogenicity. By screening a protein kinase deletion mutant library that was generated in the present work using an improved SAT1 flipper cassette, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(98 citation statements)
references
References 57 publications
4
92
0
Order By: Relevance
“…Accordingly, we hypothesized that in C. albicans , Snf1/AMPK might be activated in response to ATP drop that accompanies oxygen depletion. This is supported by our GSEA analysis that indicated a significant similarity between the transcriptional profile of snf5 and mutant of the kinase Sak1 that regulates the activity of Snf1 [53] ( Figure 7A ). Furthermore, in S. cerevisiae , Cyr1 is phosphorylated by the Snf1 to promote ATP homeostasis [54], a mechanism that might be conserved in C. albicans .…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Accordingly, we hypothesized that in C. albicans , Snf1/AMPK might be activated in response to ATP drop that accompanies oxygen depletion. This is supported by our GSEA analysis that indicated a significant similarity between the transcriptional profile of snf5 and mutant of the kinase Sak1 that regulates the activity of Snf1 [53] ( Figure 7A ). Furthermore, in S. cerevisiae , Cyr1 is phosphorylated by the Snf1 to promote ATP homeostasis [54], a mechanism that might be conserved in C. albicans .…”
Section: Resultssupporting
confidence: 60%
“…While the role of ATP sensing was not attributed to SWI/SNF complex in either microbial eukaryotes or metazoans so far, several observations support this hypothesis. Our data indicated that C. albicans SWI/SNF govern the transcriptional control of the same category of genes that are modulated to maintain ATP homeostasis in eukaryotic cells [53,66,67]. In S. cerevisiae and mammalian cells, the low-energy checkpoint Snf1/AMPK induces energy generating (beta-oxidation, carbon utilization, carnitine metabolism) and represses energy consuming reactions (fatty acid, lipid and protein biosynthesis).…”
Section: Discussionmentioning
confidence: 99%
“…These include Cox4 (a subunit of cytochrome c), Ali1 (a membrane-bound NADH-ubiquinone oxidoreduc- Carbon Pathways and Candida albicans Virulence ® tase), and Oar1 (a putative mitochondrial protein whose homologs have NADPHdependent 3-oxoacyl reductase activity) (40,42). Two mutants have known roles in other aspects of carbon metabolism, including the Snf1 complex protein Kis1 and Pex13, which is required for protein import to the peroxisome (43)(44)(45). Others had no clear connection to carbon utilization, including Pep8 (a protein involved in endosometo-Golgi transport), Swi4 (part of the SBF complex required for the G 1 /S transition), and Sin3 (a global transcriptional corepressor) (46)(47)(48)(49).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, this comparison is interesting because C. albicans is a human pathogen, so we might expect its regulation of metabolism and carbon source utilization to be different than in S. cerevisiae, a pathogen only on rare occasion. In fact, there are several unique features of C. albicans carbon regulation, such as distinctive transcriptional activators of glycolysis and alternative carbon source utilization [6,7], loss of glucose-mediated catabolite inactivation [8], and loss of glucose-responsive post-translational modifications of the regulatory kinase, Snf1 [9]. Some differences in metabolic regulation have been directly linked to virulence [8], a connection that may inform new therapeutic strategies [4].…”
Section: Introductionmentioning
confidence: 99%